Upaya Meningkatkan Hasil Belajar Siswa melalui Model Kooperatif TGT pada Pembelajaran PPKn Kelas VII - Az-zhura Az-zhura; Nyimas Nuria Hasna Anggraeni; Umi Chotimah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This PTK research was carried out by researchers as an effort by researchers to improve the quality of Indonesian education regarding the learning outcomes of class VII students at SMPN 33 Palembang which according to researchers are still low. So the effort that will be made is a cooperative model of the Team Games Tournament (TGT) type in Civics subjects. This research was conducted using a percentage descriptive research method in order to obtain good research data. Where data is collected in collaboration with Civics subject teachers and colleagues. The calculation results show that pre-cycle activities are 41.93% with a predicate of less than 65%, so as a follow-up it is necessary to improve the learning process. Next, the researcher made an alternative choice by carrying out the learning process using the TGT type cooperative model, obtaining results of 67.74% but had not achieved the target desired by the researcher, so cycle II was carried out using the TGT type cooperative. model in class VII PPKn learning at SMP Negeri 33 Palembang reached 93.54% and achieved the desired target, so this PTK was considered successful.